Agreement between cardiac output measurements by pulse wave analysis using the Pressure Recording Analytical Method and transthoracic echocardiography in patients with veno-venous extracorporeal membrane oxygenation therapy: An observational method comparison. Issue 6 (12th June 2023) - Greiwe, Gillis; Flick, Moritz; Hapfelmeier, Alexander; Winkler, Martin S.; Nitzschke, Rainer; Frings, Daniel; Saugel, Bernd
Abstract : BACKGROUND: Measuring cardiac output (CO) is important in patients treated with veno-venous extracorporeal membrane oxygenation (vvECMO) because vvECMO flow and CO need to be balanced. Uncalibrated pulse wave analysis with the Pressure Recording Analytical Method (PRAM) may be suitable to measure CO in patients with vvECMO therapy. OBJECTIVE: To assess the agreement between CO measured by PRAM (PRAM-CO; test method) and CO measured by transthoracic echocardiography (TTE-CO; reference method). DESIGN: A prospective observational method comparison study. SETTING: The ICU of a German university hospital between March and December 2021. PATIENTS: Thirty one adult patients with respiratory failure requiring vvECMO therapy: 29 of the 31 patients (94%) were treated for COVID-19 related respiratory failure. MAIN OUTCOME MEASURES: PRAM-CO and TTE-CO were measured simultaneously at two time points in each patient with at least 20 min between measurements. A radial or femoral arterial catheter-derived blood pressure waveform was used for PRAM-CO measurements. TTE-CO measurements were conducted using the pulsed wave Doppler-derived velocity time integral of the left ventricular outflow tract (LVOT) and the corresponding LVOT diameter. PRAM-CO and TTE-CO were compared using Bland–Altman analysis and the percentage error (PE). We defined a PE of <30% as clinically acceptable. RESULTS: Mean ± SD PRAM-CO was 6.86 ± 1.49 l min −1 and mean TTE-CO was 6.94 ± 1.58 l min −1 . The mean of the differences between PRAM-CO and TTE-CO was 0.09 ± 0.73 l min −1 with a lower 95% limit of agreement of −1.34 l min −1 and an upper 95% limit of agreement of 1.51 l min −1 . The PE was 21%. CONCLUSIONS: The agreement between PRAM-CO and TTE-CO is clinically acceptable in adult patients with vvECMO therapy.